Peptide-plane flipping in proteins - Hayward, Steven (Cold Spring Harbor Laboratory Press, 2001)
A peptide-plane flip is a large-scale rotation of the peptide plane that takes the φ,ψ angles at residues i and i + 1 to different structural regions in the Ramachandran plot with a comparatively small effect on the relative orientation of their side chains. This phenomenon, which is expected to play an important role during the early stages of protein folding, has been investigated using 76 proteins for which two high-resolution X-ray conformations are available. Peptide-plane flips are identified by looking for those cases where changes in |ψ(i)| + |φ(i) (+ 1)| are large (>200°), but changes in |ψ(i) + φ(i) (+ 1)| are comparatively small (<50°). Of a total of 23 cases, the most common peptide-plane flip was identified to be the type I to type II β-turn interconversion. Although individually rarer, there are many other types of flips that are collectively more common. Given the four main accessible regions α(R), α(L), β and ɛ, identified from the φ,ψ distribution corresponding to non-hydrogen-bonded peptide planes, 32 main types of peptide-plane flip are identified. Only 8 of these are "passive," in that they require only relatively minor adjustments in the orientation of adjacent peptide planes. Of these, only the type I to type II β-turn interconversion, denoted, β(i) + α(L)(i + 1) ― α(R)(i) + α(R)(i + 1), and the rarer α(R)(i) + α(L)(i + 1) ― β(i) + α(R)(i + 1), do not involve the ɛ region. "Active" peptide-plane flips affect the orientation of adjacent peptide planes. The flip, α(L)(i) + α(L)(i + 1) ― β(i) + β(i + 1), of which one example was found, shows how concerted peptide-plane flips can convert the α(L) structure to the β structure without affecting the relative orientations of the side chains.